2016
DOI: 10.1139/bcb-2015-0064
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-149 is epigenetically silenced tumor-suppressive microRNA, involved in cell proliferation and downregulation of AKT1 and cyclin D1 in human glioblastoma multiforme

Abstract: Aberrant DNA methylation has been shown to inactivate tumor suppressor genes during carcinogenesis. MicroRNA-149 (miR-149) was recently demonstrated to function as a tumor suppressor gene in glioblastoma multiforme (GBM). However, the potential linkage of miR-149 levels and the underlying epigenetic regulatory mechanism in human GBM has not been studied. We used quantitative real-time polymerase chain reaction to investigate the levels of miR-149 in GBM tissues, their matched adjacent normal tissues, and gliob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…It has been reported that miR-149-5p can inhibit cell proliferation, invasion and migration in human hepatocellular carcinoma by targeting AKT1 and further facilitating the mTOR pathway [38]. The interaction between miR-149-5p and AKT1 is also reported in colon carcinoma and glioblastoma [39, 40]. Based on the assumption that circNRIP1 plays a tumour promotor role in GC through the classic ceRNA mechanism, we tried to identify the ceRNA of circNRIP1, which should also be the downstream target gene of miR-149-5p.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that miR-149-5p can inhibit cell proliferation, invasion and migration in human hepatocellular carcinoma by targeting AKT1 and further facilitating the mTOR pathway [38]. The interaction between miR-149-5p and AKT1 is also reported in colon carcinoma and glioblastoma [39, 40]. Based on the assumption that circNRIP1 plays a tumour promotor role in GC through the classic ceRNA mechanism, we tried to identify the ceRNA of circNRIP1, which should also be the downstream target gene of miR-149-5p.…”
Section: Resultsmentioning
confidence: 99%
“…2, 25 2 It has been well established that miR-149 is epigenetically silenced in GBM, and its overexpression not only suppresses tumor cell proliferation but also increases the sensitivity of cancer cells to chemotherapy. [26][27][28][29] We, therefore, investigated the role of SLC16A1-AS1 in GBM and its potential interaction with miR-149 in this study.…”
Section: Introductionmentioning
confidence: 99%
“…found that 5-Aza-CdR in combination with histone deacetylase inhibitor trichostatin A (TSA) could increase miR-200c in LY2 cells. In GBM, Ghasemi et al 69 . revealed that treatment of U87MG cells with 5-Aza-CdR can reverse the hypermethylation status of miR-149 and increase its expression, thus decreasing target mRNA and protein levels.…”
Section: Resultsmentioning
confidence: 99%